On the combination of water emergency wells and mobile treatment systems: a case study of the city of Berlin - Christoph Stallkamp; Florian Diehlmann; Markus Lüttenberg; Marcus Wiens; Rebekka Volk; Frank Schultmann (Annals of Operations Research, 2020)
A shortage of water leads to severe consequences for populations. Recent examples like the ongoing water shortage in Kapstadt or in Gloucestershire in 2007 highlight both the challenges authorities face to restore the water supply and the importance of installing efficient preparedness measures and plans. This study develops a proactive planning approach of emergency measures for possible impairments of water supply systems and validates this with a case study on water contamination in the city of Berlin. We formulate a capacitated maximal covering problem as a mixed-integer optimization model where we combine existing emergency infrastructure with the deployment of mobile water treatment systems. The model selects locations for mobile water treatment systems to maximize the public water supply within defined constraints. With the extension to a multi-objective decision making model, possible trade-offs between the water supply coverage and costs, and between the coverage of differently prioritized demand points are investigated. Therefore, decision makers benefit from a significantly increased transparency regarding potential outcomes of their decisions, leading to improved decisions before and during a crisis.
Keywords: 000; Humanitarian logistics; Water contamination; Emergency wells; Disaster; GIS; Optimization